Rumination Patterns, Positive and Negative Changes among Primary Caregivers of Cancer Patients in Pakistan - Eiman Nizam; Naeem Aslam (Pakistan Journal of Medical Research, 2025)
Background: Cancer being characterized as a chronic illness not only affects the patient but also the person who provides care for them. The traumatic experience of its diagnosis poses both positive and negative changes among primary caregivers.